Prevalence and Associated Risk Factors of Depression among Elderly People Admitted in a Tertiary Health Care Centre of Nepal - Dhakal, Bijaya; Lamichhane, Rama Kumari; Sapkota, Kalyan; Thapa, Aasha (Journal of National Heart and Lung Society Nepal, 2023)
Background: Ageing is associated with various physiological and pathological changes including Mental Health. Mental health is a neglected health problem in Nepal which is underdiagnosed and undertreated, especially among elderly population. However, Depression among elderly people is the most common mental health problem worldwide and in Nepal, Limited research has been conducted. Thus, study aimed to assess the prevalence and associated factors of depression among elderly admitted in tertiary level hospital, Nepal. Methods: Descriptive cross-sectional study design was used where 330 patients aged 60 years and over and admitted in geriatric ward were purposively selected as sample of the study. Data were collected from September 2021 to March 2022 semi structured face to face interview schedule questionnaire to identify sociodemographic characteristics as well as factors associated with depression and Geriatric depression scale item 15 (GDS 15) to measure prevalence of depression. Data were entered in SPSS, analyzed using descriptive and inferential statistics and presented in tables. Results: This study had prevalence of depression 65.8%. Male had higher prevalence rate of depression than female. Prevalence of depression was significantly associated with gender, education status, financial support from family (P-value=0.010, 0.042 and 0.00) at 95% of confidence interval. Conclusion: The prevalence of depression among older adult was found to be high. This emphasizes the need for screening of depression among elderly, to initiate early intervention measures.